A function, f(x)=1x+4

𝑓
(
π‘₯
)
=
1
π‘₯
+
4
, is reflected. Its image is the function g(x)=βˆ’1xβˆ’4
𝑔
(
π‘₯
)
=
βˆ’
1
π‘₯
βˆ’
4
. Select the rule used to reflect the function.(1 point)
Responses

ryβˆ’axis
π‘Ÿ
𝑦
βˆ’
π‘Ž
π‘₯
𝑖
𝑠
r subscript y axis baseline

ry=4
π‘Ÿ
𝑦
=
4
r subscript y equals 4 baseline

ry=βˆ’4
π‘Ÿ
𝑦
=
βˆ’
4
r subscript y equals negative 4 baseline

rxβˆ’axis

1 answer

To determine the rule used to reflect the function \( f(x) = \frac{1}{x} + 4 \) to get \( g(x) = -\frac{1}{x} - 4 \), we should look at the transformations involved.

  1. Reflection over the \( x \)-axis would change the sign of the entire function. In this case, \( f(x) \) changes to \( -f(x) \).
  2. The term \( +4 \) in the function \( f(x) \) is a vertical shift upward. The reflection over the \( x \)-axis will also affect this constant term, making it \( -4 \) instead of \( +4 \).

The transformation from \( f(x) = \frac{1}{x} + 4 \) to \( g(x) = -\frac{1}{x} - 4 \) indicates that the reflection is with respect to the \( x \)-axis.

Therefore, the correct response is:

rxβˆ’axis